Rural-urban fringe of Edinburgh 1850 - 1967 - Strachan, Alan James (The University of Edinburgh, 1969)
The rural-urban fringe is that zone around a city into which the urban area is expanding, but which still retains much of its agricultural and open space character. Studies of this transitional area have been carried out around maiy cities in North America whereas British cities have hot been so intensively investigated. An historical study was undertaken to establish whether or not a fringe existed prior to the introduction of the automobile, since many American researchers have attributed the emergence of this zone to the increased personal mobility made possible by widespread car ownership. In order to determine the character and changes which have taken place in the form of urban growth an analysis was made of Edinburgh at twenty year intervals after 1850. At each period the inner fringe boundary was delimited,forming a line outwards from which the spread of urban land uses could be identified. In addition a study was made of the degree of agricultural orientation towards the Edinburgh market at ten year intervals after 1866. These detailed investigations established the fact that during tho 19th century urban growth was limited to the immediate vicinity of the built-up area, beyond which was a scatter of institutions and several villages whioh had begun to assume a dormitory role. In contrast to this restricted zone of urban expansion poor transport facilities for bulky and perishable agricultural produce gave rise to a wide ring of urban oriented farming activity. After 1900 improved transportation media allied with a demand for houses with gardens in semi-rural surroundings led to a rapid outward growth of Edinburgh along the main roads reaching out to and beyond the older dormitory villages. The growing demand for recreation facilities resulted in the multiplication of perks, playing fields and golf courses, which along with many institutions and agriculture infilled the interstices between the tentacles of urban growth. The implementation of planning legislation in 1947 brought free urban expansion to an end and resulted in the infilling of the star pattern giving rise to a compact urban area around which a Green Belt of agricultural, recreational and institutional land uses was established. This restricted area has forced new urban expansion out of the towns and villages beyond the belt giving rise to a ring of satellite settlements quite separate from the city. Improved transport has negated the necessity for agriculture to depend on the adjacent urban market. This means that the fringe area at the present time is dependent on a few rural land uses which contrasts with the important role played by agriculture during the 19th century. The form and process of urban growth over the last one hundred years, which had been identified with reference to Edinburgh, were then compared with the more extensively documented rural urban fringe areas around North American cities. In this comparison the differences and similarities between them were highlighted and wherever possible accounted for. In the appendices a full account is given of the premises used in delimiting the inner boundary of the fringe as well as functions and area which should be investigated in order that the area! extent of the rural-urban fringe around cities in the United Kingdom may be determined.